Analysis of partitioned methods for the Biot System. Issue 6 (18th February 2015) - Bukac, Martina; Layton, William; Moraiti, Marina; Tran, Hoang; Trenchea, Catalin
<x xml:space="preserve">Abstract</x> In this work, we present a comprehensive study of several partitioned methods for the coupling of flow and mechanics. We derive energy estimates for each method for the fully‐discrete problem. We write the obtained stability conditions in terms of a key control parameter defined as a ratio of the coupling strength and the speed of propagation. Depending on the parameters in the problem, give the choice of the partitioned method which allows the largest time step. © 2015 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq 31: 1769–1813, 2015